Continuity of Care: Perspectives of Uninsured Free Clinic Patients. (December 2019) - Kamimura, Akiko; Panahi, Samin; Ahmmad, Zobayer; Stoddard, Mary; Weaver, Shannon; Ashby, Jeanie
Background: Continuity of care is vital to the success of a health-care system because it improves patient satisfaction and health outcomes, and reduces hospitalizations and emergency room visits. Objective: The purpose of this study was to examine free clinic patients' perspectives of continuity of care in the United States. Method: A convenience sample of free clinic patients who were the age of 18 or older and spoke English or Spanish participated in a self-administered survey from January to April in 2017 (N = 580). Results: Better instructions from providers were associated with higher levels of continuity of care ( P < .01). Higher levels of stress and worse self-rated general health were related to lower levels of continuity of care ( P < .05 for stress, P < .01 for general health). Being employed was associated with lower levels of continuity of care ( P < .05). Non-US born English speakers and Spanish speakers rated continuity of care higher than US born English speakers ( P < .01). Conclusion: Even if a patient is unable to see the same physician over time, quality instructions from a well-coordinated provider team may enhance continuity of care from patient perspectives. The social context of patients such as working poor individuals is very important for providers to understand in order to identify barriers to continuity of care.